THE AMBIGUITY OF PEACE NARRATIVES IN RELIGIOUS COMMUNITIES OF WEST KALIMANTAN - Hidayat, Samsul; Sulaiman (Living Islam: Journal of Islamic Discourses, 2023)
Abstract A lot of conflicts have occurred in West Kalimantan, and the latest was the anarchic treatment of the Ahmadiyya and the Gafatar. This study seeks to explain the ambiguity of peace narratives in a plural society in West Kalimantan, and to find out the community's response to such conflicts. This study is qualitative-descriptive research which was conducted through collecting observational data, making documentation, and doing literature studies, analyzing data using data display, reducing data and drawing conclusions. The results of this study showed that West Kalimantan is known for its plural society and for voicing for peace, but there are still various conflicts in the form of anarchy in religious communities. This study concluded that the response of the people of West Kalimantan is relatively different; some see conflict positively especially those who have interests in it, and negatively especially those who feel disadvantaged. The ambiguity of peace narratives can be seen when individual or group interests are the main consideration in peace-building. The advocated peace is merely an empty discourse in a plural society that is unable to manage conflict. The ambiguity of peace narratives, which is still rife with conflicts from religious anarchy, is caused by the religious leaders, the government and the religious communities not working together to build peace. Keywords: Ambiguity, Peace, Religion. Abstrak Berbagai konflik yang terjadi di Kalimantan Barat yang terakhir bentuk perlakukan yang anarkis terhadap kelompok Ahmadiyah dan Gafatar. Penelitian ini menjelaskan tentang keambiguan narasi perdamaian di tengah masyarakat majemuk di Kalimantan Barat. Serta melihat respon masyarakat terhadap konflik-konflik yang terjadi pada masyarakat majemuk di Kalimantan Barat. Penelitian ini termasuk ke dalam klister kualitatif-diskriptif dengan cara pengumpulan data observasi, dokumentasi, serta kajian-kajian pustaka, analisis data menggunakan display data, reduksi data dan menarik kesimpulan. Hasil penelitian ini menunjukan bahwa Kalimantan Barat terkenal dengan mayarakat yang majemuk dan mensuarakan perdamaian akan tetapi masih ada berbagai konflik yang berbentuk keanarkisan masyarakat beragama. Kesimpulan penelitian ini bahwa respon masyarakat Kalimantan Barat sangat relatif, ada yang melihat konflik secara positif bagi yang mempunyai kepentingan dan berbentuk negatif bagi yang merasa dirugikan. Keambiguan narasi perdamaian nampak ketika kepentingan individu atau kelompok menjadi pertimbangan utama dalam merajut perdamaian. Perdamaian yang dijunjung tinggi hanya isu belaka dalam masyarakat majemuk yang tidak mampu mengelola konflik. Kembiguan narasi perdamain yang masih maraknya terjadi konflik dari keanarkisan umat beragama, hal ini disebabkan oleh para tokoh agama, pemerintah dan umat beragama tidak bergandengan untuk merajut perdamaian. Kata Kunci: Ambiguitas, Perdamaian, Agama.